Simulação da secagem de bagaço de laranja em leito de jorro por um modelo em cascata usando softwares gratuitos - Sgobi, Marcus Vinicius (Universidade Federal de São Carlos, 2024)
Due to the increasing consumption and production of orange derivatives, a large amount of biomass, generically known as bagasse, is generated. This biomass has potential for several applications, such as use for animal feed or combustion, but all of them require a drying step. Among the various methods that can be used to carry out this drying, one that has accumulated a considerable volume of studies is that of the spouted bed, which, despite its disadvantages, has always proven to be quite viable on a small scale and even on a medium scale. . However, before any chemical process is consolidated, a simulation stage is required, which aims to mathematically describe the physical reality. Having a fully developed model valid for a wide range of conditions makes it possible to advance in certain stages of consolidating the drying process, such as developing an efficient control system and increasing scale. The objective of this Undergraduate Work was to develop and simulate an adaptive model and concentrated parameters for drying orange pomace in a spouted bed using free software, and subsequently carry out the validation of such a model, comparing the simulated results with data experimental trials available in advance. As far as it was possible to reach, with the short time available for the development of a very challenging TG, unfortunately, the experimental validation was not satisfactorily completed, as a very specific flaw in the code was identified that prevented the completion of this stage.
Simulation of orange juice waste drying in a spouted bed using a free software
Keywords: Secagem; Biomassa; Modelagem; Leito de jorro; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA